The Effect Of Tik Tok Applications On The Imitation Behavior Of Communications Science Students Faculty Of Social Science UINSU - Nasoruddin (International Journal of Cultural and Social Science, 2022)
The Tik Tok application is very popular with Indonesian people in various circles, both teenagers, young people, as well as adults. There are also communication science students at the North Sumatra State Islamic University (UIN SU) who are very fond of playing Tik Tok, especially during this pandemic, students study online so there are fewer activities outside the home. To fill their spare time, students mostly play Tik Tok, both Tik Tok which has negative and positive content, such as dancing with various Tik Tok music, to taking part in the challenge of taking off clothes with music. To get a lot of viewers, likes and followers. So that researchers are interested in researching this Tik tok addiction, with the aim of knowing how the influence of the Tik tok application on changes in the imitative behavior of communication science students. The method used by the researcher is a quantitative research method. -Daily there are 31% of the data that has been obtained by student researchers there is a change in their behavior, both in singing songs, doing Tik tok movements every day, and respondents feel that Tik tok movements are common in everyday life.